"I live one day at a time": Future orientation among Muslim high school dropouts in Israel. (December 2020) - Shoshana, Avihu
Highlights: This article offers a phenomenological examination of the future orientation of Muslim high school dropout youth in Israel. This research is important in light of the multiple social exclusions, or structural vulnerabilities, these youths experience. The study's findings reveal three prominent future orientations: a refusal to engage in the future; a closed future; and a primary aspiration to become solo self-employed. The discussion expands on the impact of the youths' structural vulnerability on their future orientation, and the linkages between culture, future orientation, and inequality. Abstract: This article offers a phenomenological examination of the future orientation of 24 Muslim male high school dropout youth in Israel. This research is important in light of the multiple social exclusions, or structural vulnerabilities, these youths experience on the basis of poverty, stigmatized religious-national identity, and dropping out of school. The study's findings reveal three prominent future orientations: a refusal to engage in the future and a preference for examining the present; a closed future (expressed as a strong belief that the distant future will likely resemble the present); and a primary aspiration to become solo self-employed (i.e., occupationally independent), along with a unique rationale for explaining this aspiration. The Discussion expands on the impact of the youths' structural vulnerability on their future orientation, the symbolism of their aspiration to be self-employed in the future, and the linkages between culture, future orientation, and inequality.